Draft Annual Plan 2003-2004 Vol. I Government of Karnataka - Planning Commission (Planning Commission, 2003)
The outlay for the Annual Plan 2003-04 is Rs.9127.52 crores. This represents an increase of 6% over the budgetted outlay of Rs.8610.61 crores in 2002-03 and forms 21% of the Tenth Plan outlay of Rs.43558.22 crores. The District Plan size for Annual Plan 2003-04 has been proposed at Rs.668.08 crores. The outlay proposed for Externally Aided Projects in Annual Plan 2003-04 is Rs. 1537.62 crores.
Planning, Statistics and Science and Technology Department